Organizational Change and Change Readiness: Employees’ Attitudes during Times of Saudi Electric Organizational Shift - Anar Aljudhei; Randolf Von N. Salindo (International Journal of Engineering and Management Research, 2018)
The study aimed to assess the Organizational Change and Change Readiness in Saudi Electric Company: Employees attitude during time of Company Organizational Shift. Specifically, the study answered the level of implementation of change management at Saudi Electric Company as perceived by the respondents in terms of communication, employee Involvement, employee Training and stress Management. Also, the study answered the Level of Effectiveness of change management at Saudi Electric Company as perceived by the respondents in terms of employee motivation, decision making and employee performance. This study further focused on the relationship between status & level of effectiveness of implementation of change management at Saudi Electric Company. The study also analyzed the employee attitude and readiness for change management in the organization. According to the limitation of this study are shortage of time and shortage of available data, moreover the result of this study is related to Saudi Electric Co in Saudi Arabia only, so it may not fit with all other organizations that may have different in size and different in nature of business.